Exchange Rates, Country Preferences, and Gold - Isard, Peter (IMF Working Papers; Working Paper ;, 1992)
This paper provides indirect tests of the hypothesis that exchange rate movements may be largely coterminus with changes in preferences for holding claims on different countries. It is argued that changes in country preferences will be reflected systematically in the price of gold and, hence, that gold price movements, under the maintained hypothesis, should have explanatory power with respect to exchange rate movements over and above the effects of monetary shocks. The paper applies multivariate vector autoregression and cointegration modeling techniques to test for the short-and long-run influence of gold prices on exchange rates conditional on other monetary and real macroeconomic variables, and applies the resulting error correction exchange rate equation to out-of-sample forecasting exercises.